Cosmeceutical Potential of Major Tropical and Subtropical Fruit By-Products for a Sustainable Revalorization - Abigail García-Villegas; Alejandro Rojas-García; María del Carmen Villegas-Aguilar; Patricia Fernández-Moreno; Álvaro Fernández-Ochoa; María de la Luz Cádiz-Gurrea; David Arráez-Román; Antonio Segura-Carretero (MDPI AG, 2022)
The increasing production of tropical fruits followed by their processing results in tons of waste, such as skins or seeds. However, these by-products have been reported to be rich in bioactive compounds (BACs) with excellent properties of interest in the cosmeceutical industry: antioxidant, anti-aging, anti-inflammatory, antimicrobial and photoprotective properties. This review summarizes the tropical fruits most produced worldwide, their bioactive composition and the most important and studied therapeutic properties that their by-products can contribute to skin health, as well as the different approaches for obtaining these compounds using techniques by conventional (Soxhlet, liquid-liquid extraction or maceration) and non-conventional extractions (supercritical fluid extraction (SFE), ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), pressurized liquid extraction (PLE) and two-phase aqueous system), followed by their identification by HPLC-MS or GC-MS analysis. Moreover, this work encompasses several studies that may prove the effects of seeds and skins from tropical fruits against oxidative stress, hyperpigmentation, acne, aging or UV radiation. Therefore, the investigation of functional components present in tropical fruit by-products under a circular bioeconomy model could be of great interest for the cosmeceutical industry and a very promising option for obtaining new cosmeceutical formulations.